Enhancing Student Emotional Intelligence with Ludo Emosi: An Effective Experiential Learning Model for Group Guidance - Fauziah Fauziah; Siti Partini Suardiman; Dody Hartanto; Akhmad Fajar Prasetya; Alif Muarifah; Wahyu Nanda Eka Saputra; Muya Barida; Agus Ria Kumara (Journal of Education and Counseling (JECO), 2026)
Low emotional intelligence is a significant problem that hinders the social and academic development of high school students, where conventional guidance methods often fail to engage students effectively. This study aims to evaluate the effectiveness of an innovative group guidance intervention model that uses the Ludo Emosi game media in the Experiential Learning framework to improve students' emotional intelligence. This study used a pre-experimental, one-group pretest-posttest design involving eight 11th-grade students with low to moderate levels of emotional intelligence. The intervention was carried out in three structured sessions following Kolb's learning cycle, namely concrete experience, reflective observation, abstract conceptualization, and active experimentation. The results showed a statistically significant increase in participants' emotional intelligence scores from before (pretest, M=19.12) to after (posttest, M=51.75), as evidenced by the Paired Samples t-test (t(7) = -15.76, p < 0.001). Furthermore, the N-Gain Score analysis produced a value of 0.80, indicating that the intervention had a practical effectiveness level classified as “High.” These findings demonstrate that a game-based experiential learning approach can effectively improve students' emotional skills and provide a practical, validated intervention model for guidance and counseling teachers.